Apical pelvic organ prolapse repair via vaginal‐assisted natural orifice transluminal endoscopic surgery: Initial experience from a tertiary care hospital. Issue 3 (23rd September 2020) - Alay, Ismail; Kaya, Cihan; Cengiz, Huseyin; Yildiz, Sukru; Aslan, Ozgur; Yasar, Levent; Ekin, Murat
Abstract: Introduction: Natural orifice transluminal endoscopic surgery has been used for gynecologic operations in recent years. The aim of the study is to describe our initial experience using vaginal‐assisted natural orifice transluminal endoscopic surgery (vNOTES) for apical pelvic organ prolapse repair. Methods: After patients underwent vaginal hysterectomy, vNOTES sacrocolpopexy (n = 4) or vNOTES high uterosacral ligament suspension (n = 7) were performed to treat symptomatic apical pelvic organ prolapse. Sociodemographic and clinical characteristics, Pelvic Organ Prolapse Quantification results, and recorded surgical data (eg, duration of surgery, intraoperative complications, additional prolapse and incontinence surgeries) were obtained from patient files and the hospital's database. Information from postoperative follow‐up visits, including complications and anatomical results, were also recorded. Results: The mean age of the patients was 60.7 ± 9.1 years. The mean total operative time was 121.3 ± 22.7 minutes. The mean operative time for vaginal hysterectomy, vNOTES sacrocolpopexy, and vNOTES uterosacral ligament suspension was 46 ± 11.9, 65 ± 38, 25 ± 8.2 minutes, respectively. There were no intraoperative and postoperative complications observed. The mean postoperative 24‐hour visual analog scale score was 3.5 ± 1.9 for vNOTES sacrocolpopexy patients and 3.2 ± 0.9 for vNOTES uterosacral ligament suspension patients. Only one patient in the vNOTES sacrocolpopexy group had a recurrence; she experienced stage 2 anterior compartment prolapse 8 months after surgery. Conclusion: As a treatment for apical pelvic organ prolapse, vNOTES is a feasible approach in both sacrocolpopexy and uterosacral ligament suspension.